E-MONEY REGULATIONS AND COMPARISON BETWEEN INDONESIA AND HONG KONG - Ku Yun Yin; Aluisius Hery Pratono; Njoto Benarkah (CALYPTRA, 2021)
Purpose— The purpose of this research is to find out the differences and similarities in two different regions: Indonesia and Hong Kong. Design/methodology/ approach— Data is collected from various of sources, from online journals, published journals, to online news etc. Because this thesis is trying to bring the latest informations as possible, so online news are one of the essential sources. Findings— The findings revealed the e-wallet facilities’ differences and similarities in two regions, in terms of facilities coverage, maturity and ease of use and adoption. Value— For the benefits of audiences, this thesis is providing some of the latest informations we could find online by the time this thesis is written, for the best of author’s knowledge. Keywords E-Wallet, Indonesia, Hong Kong, E-Money, Financial, Regulation, Qualitative, Comparison Paper type Research paper